Thunderstorm Downbursts and Wind Loading of Structures: Progress and Prospect - Solari, Giovanni (Frontiers in Built Environment, 2020)
In 1961, Davenport published a paper, considered by most a constitutive deed of wind engineering, in which meteorology, micrometeorology, climatology, aerodynamics and structural dynamics were embedded in a homogeneous framework of the wind loading of structures. This framework, known as Davenport chain and based on a wind model coherent with synoptic-scale extra-tropical cyclones, is so limpid and elegant as to become, in the course of the years, a sort of axiom. Between 1976 and 1978 Gomes and Vickery separated thunderstorm from non-thunderstorm winds, determined their extreme wind speed marginal distributions and from them derived a mixed statistical model later extended to other wind phenomena. This viewpoint, dealt with as a milestone in the emerging issue of mixed climatology, proved the impossibility to label a heterogeneous range of phenomena endowed with different velocity fields, frequencies, durations and sizes by the generic term “wind”. Many wind types, in particular tropical cyclones, tornadoes and downslope winds, occur in limited and well-known areas. Extra-tropical cyclones and thunderstorms are natural hazards that affect the whole planet. This paper provides a state-of-the-art about thunderstorm downburst, one of the most spectacular and damaging events produced by nature, and its wind loading of structures. Also in the light of planet's climatology evolution, this topic is a key issue of structural safety and sustainability.